Relationship between ground reaction force and sacrum acceleration during 180° change of direction maneuvers in elite female basketball players - Ogata, H.; Yamashita, D.; Nishikawa, N.; Yokozawa, T.; Hoshikawa, M. (Frontiers in Sports and Active Living, 2026)
Background: This study investigated the relationship between sacrum acceleration (ACCIMU) measured using an inertial measurement unit (IMU) and ground reaction force (GRF) measured using force plates during 180° change of direction (COD) maneuvers in elite female basketball players.